Effects of adding N2-fixing Rhodopseudomonas palustris to stimulate the growth and yield of canary melon (Cucumis melo L.). - Le Minh Tuan; Nguyen Phuong Truc Huyen; Vo Thi Bich Thuy; Le Thanh Quang; Le Thi My Thu; Nguyen Thi Xuan Dao; Tran Chi Nhan; Ly Ngoc Thanh Xuan; Nguyen Quoc Khuong (PLoS ONE)
This study evaluated the effects of a mixture of four N2-fixing strains of Rhodopseudomonas palustris-VNW64, VNS89, TLS06, and VNS02-(PNSB) on soil properties, nitrogen (N) uptake, plant growth, and yield of canary melon cultivated in alluvial soil. A greenhouse experiment was conducted using a completely randomized block design with eight treatments: (i) 100% N of recommended fertilizer formula (RFF), (ii) 85% N of RFF, (iii) 70% N of RFF, (iv) 100% N of RFF + PNSB, (v) 85% N of RFF + PNSB, (vi) 70% N of RFF + PNSB, (vii) PNSB only, and (viii) no fertilization. The application of PNSB improved soil pH and available N concentrations. The highest N uptake (33.9 kg N ha ⁻ ¹) was recorded in the 100% RFF + PNSB treatment. Notably, the 70% RFF + PNSB treatment achieved comparable N uptake (27.7 kg N ha ⁻ ¹) to the 100% RFF treatment (28.6 kg N ha ⁻ ¹). The 85% RFF + PNSB treatment maintained plant height and yield equivalent to the 100% RFF treatment. These results suggest that supplementing with PNSB can reduce N fertilizer application by up to 15% without compromising crop performance. The PNSB mixture should be further tested under a field trial.